Social Integration and Health-Related Quality of Life of Elderly Referred to a Health Center in Sabzevar - Mojtaba Laal Ahangar; Homeyra Sajjadi; Ahmad Ali Akbari Kamrani (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives Old age is a period of life in which elderly are exposed to potential threat. These factors lead to decreased quality of life in elderly. Social interaction is of the factors affecting the quality of life and health in the elderly. We aimed to assess the relationship between social integration and health-related quality of life in seniors in Sabzevar city. Methods & Materials This descriptive study was performed on 135 elderly referred to a health center city in Sabzevar using the proportional sampling method. Data collection tools included health-related quality of life questionnaire (SF-36) and a researcher made questionnaire regarding the participants' social integration and demographic information. Data were analyzed by descriptive statistics, and Pearson's correlation, T, Mann-Whitney and ANOVA tests. Results The mean±SD score for social integration in the elderly was 30.6±9.5 (33.26±9.4 in men and 27.46±9.6 in women) which was average. The mean±SD health-related quality of life scores in physical and mental health domains were 10.87±2.65 and 11.41±2.96, respectively. There was a significant positive correlation between social integration and health-related quality of life (r=0.73, P<0.001). Also there was a significant correlation between social integration and age (r=-0.3, P=0.001), marital status (P<0.001), employment (P<0.001), sex (P<0.001), and education level (r=0.4, P=0.003). Conclusion Policy makers can plan interventions in the field of social integration to improve the quality of life in the elderly.